‘Semipelagianism’: The Origins of the Term and its Passage into the History of Heresy - Backus, Irena (The journal of ecclesiastical history, 2014)
The term ‘Semipelagianism’ is usually taken to refer to fifth- and sixth-century teachings of Hadrumetum and Massilian monks. The term originated, however, with sixteenth-century Protestants who used it to describe a view of salvation by human effort in combination with grace. Theodore Beza invented the term in about 1556, applying it to the Roman Catholic view of grace and human will. The Lutheran Formula of Concord (1577) used it to designate Lutheran synergists. Initially, therefore, the term referred to contemporaneous teachings. Starting with Nicholas Sanders (1571), however, Roman Catholics introduced a shift of meaning, with fifth-century Massilians becoming the central connotation.